Protein profile of the ovarian follicular fluid of brown brocket deer (Mazama gouazoubira; Fisher, 1814) - Souza, Thais T. S. (2020)
The aim of this study was to characterize the protein profile of ovarian follicular fluid (FF) of brown brocket deer (Mazama gouazoubira). Five adult females received an ovarian stimulation treatment and the FF was collected by laparoscopy from small/medium (<= 3.5 mm) and large (>3.5 mm) follicles. Concentrations of soluble proteins in FF samples were measured and proteins were analyzed by 1-D SDS-PAGE followed by tryptic digestion and tandem mass spectrometry. Data from protein list defined after a Mascot database search were analyzed using the STRAP software tool. For the protein concentration, no significant difference (P> 0.05) was observed between small/medium and large follicles: 49.2 +/- 22.8 and 56.7 +/- 27.4 mu g/mu l, respectively. Mass spectrometry analysis identified 13 major proteins, but with no significant difference (P> 0.05) between follicle size class. This study provides insight into elucidating folliculogenesis in brown brocket deer.